Rare case of difficult intubation: lingual tonsillar hypertrophy : case report - Ghazali, Abdul Majid; Singh Sran, Surrej Darshain; Ti, Phing Phang; Azmi, Nurul Izzah (Malaysian Medical Association, 2023)
We report a case of unanticipated difficult intubation due to lingual tonsillar hypertrophy. This is a case of a 45-year-old lady with hypertension undergoing Scarf Osteotomy and Wedge osteotomy right first metatarsal bone and soft tissue McBride procedure due to Bilateral hallux valgus stage 4 under general anaesthesia. Preoperative airway assessment did not suggest a potentially tricky airway case. After an uneventful induction, 3 attempts to intubate via direct laryngoscopy and video laryngoscopy were undertaken; however, they failed due to poor view. Attempts to ventilate with a supraglottic airway device failed also, and the decision was made to reverse the patient and postpone surgery after investigating the reason for the difficult airway. After Ear, Nose, and Throat (ENT) assessment, it was ascertained that this patient's difficult intubation was due to lingual tonsil hypertrophy. Lingual tonsil hypertrophy is frequently asymptomatic and can be an anaesthetic emergency if undiagnosed before anaesthesia. Lingual tonsil hypertrophy causes difficulty in ventilation and intubation. Fibreoptic intubation will be the preferred airway management option for general anaesthesia patients with known lingual tonsil hypertrophy.